Disaster-Resilient Design of Manufacturing Facilities Through Process Integration: Principal Strategies, Perspectives, and Research Challenges - El-Halwagi, Mahmoud M.; Sengupta, Debalina; Pistikopoulos, Efstratios N.; Sammons, Jeff; Eljack, Fadwa; Kazi, Monzure-Khoda (Frontiers in Sustainability, 2020)
Extreme events cause significant damage and disruption to the manufacturing sector, associated supply chains, and adjacent communities. These disastrous shocks may include natural disasters (e.g., hurricanes, floods, earthquakes), pandemics, catastrophic economic collapses (e.g., price crash of oil and gas), and terrorist and cyber attacks. Although much research has addressed the resilience of infrastructure, very little work has targeted the resilience of the manufacturing processes. Even less work has addressed the topic of process design approaches to create disaster-resilient industrial processes. The objective of this paper is to provide perspectives on the use of process integration for developing disaster-resilient designs of industrial plants with focus on the process industries (e.g., chemical, petrochemical, oil, gas, specialty chemicals, pharmaceuticals, biorefining). Focus is given to three categories of extreme events: natural disasters, pandemics, and economic collapses. Although several principles have been proposed for resilience engineering of infrastructure, industrial processes have unique features that warrant a tailored discussion. To streamline the discussion, we have identified 12 principal strategies for creating disaster-resilient designs: Fail-safe by design, (2) Redundancy, (3) Reconfigurability, (4) Modularity/Mobility/Distributability, (5) Repurposability, (6) Flexibility, (7) Controllability, (8) Reliability, (9) Recoverability/restorability, (10) Rapidity, (11) Robustness, and (12) Resourcefulness. These strategies are generally applicable to the process industries because they transcend the specific type of the manufacturing facility. Examples of industrial applications are given to explain the resilience strategies and discuss the research challenges and potential use of process integration in the systematic development of design concepts and tools for resilient design. The paper concludes with a list of future directions and promising research opportunities.